Effect of Kyphoplasty in the Treatment of Osteoporotic Vertebral Fractures Compared to Vertebroplasty – Overview of Systematic Reviews - Botelho, Ricardo Vieira; Diniz, Juliete Melo; Sousa, Ulysses de Oliveira; Mudo, Marcelo Luís; Oliveira, Matheus Fernandes de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Vertebroplasty and kyphoplasty are possible options for vertebral augmentation after osteoporotic fractures. Both are percutaneous techniques with specific advantages and disadvantages. Our aim is to compare the clinical and radiological results of these two procedures. Methods An overview of published systematic reviews in the literature on the effects of kyphoplasty compared with vertebroplasty was performed.Results After short and long follow-up, the kyphoplasty group had lower pain scores on the visual analogue scale (VAS), lower scores in the Oswestry Disability index (ODI), greater restoration of the vertebral body height and lower kyphosis angle in the immediate postoperative period. There was less leakage of cement to the vertebral canal and extraspinal spaces.Conclusions Compared with vertebroplasty, kyphoplasty achieved better results in pain relief, quality of life, correction of spinal deformity and lower risk of cement leakage.
Keywords: kyphoplasty; vertebroplasty; vertebral fracture; osteoporosis